Pengembangan Bahan Ajar Tema "Aku Cinta Indonesia" Untuk Mendukung Kualitas Pembelajaran - Anindya Putri; Darsinah (Jurnal Pendidikan Anak Usia Dini Undiksha, 2023)
The Independent Curriculum changes learning orientation, so teachers must adapt. This research aims to develop teaching materials on the theme I Love Indonesia. This type of research is Research and Development (RnD) research using the ADDIE method. Data was collected using a questionnaire via Google Forms at the analysis stage. The subjects involved in this research were 13 kindergarten teachers at the analysis stage, 6 validators, 2 class teachers, 2 school principals, teaching materials expert lecturers, and curriculum expert lecturers at the feasibility test stage. Data collection methods use observation and questionnaires. The data collection instrument uses a questionnaire. The data analysis technique in this research is qualitative and quantitative descriptive data analysis technique. The research results are I Love Indonesia, comprising the sub-themes of Culture and Natural Wealth. The Culture subtheme contains sub-subthemes such as physical culture. Behavioral Culture and Idea Culture. The sub-subtheme of Natural Wealth contains Water and Land. It was concluded that 100% of respondents needed developing teaching materials on the theme I Love Indonesia for educators in quality learning using the Independent Curriculum. 100% of class teachers understand the guidelines for developing teaching materials on I Love Indonesia.